A graspable olfactory display for virtual reality. Issue 169 (January 2023) - Niedenthal, Simon; Fredborg, William; Lundén, Peter; Ehrndal, Marie; Olofsson, Jonas K.
Highlights: We present a novel compact, low-cost olfactometer that is fitted to the hand controller of the HTC vive virtual reality (VR) system. The olfactometer employs stepless valves to enable control of scent magnitude and blending. Our olfactometer allows for concealed (i.e., unknown to the user) combinations of odours with virtual objects and contexts, making it well suited to applications involving active sniffing and interrogation of objects in virtual space for recreational, scientific, or therapeutic functions. We have utilized the opening in the HTC vive hand controller as a channel to output scent at the hand, linking physical smells to a synthetic VR environment. Our device introduces proportional blending through stepless valves, allowing for the creation of more nuanced blends from a basic set of four available scents. A gas sensor study indicates that the device captures many of the characteristics of high-end research olfactometers in a low-cost, handheld form factor. A user study in a virtual wine cellar game demonstrates that the device is intuitive to use and stable enough for long-term smell training sessions. Abstract: The sense of smell, olfaction, is seldom engaged in digital interactive systems, but, supported by the proper technology, olfaction might open up new interaction domains. Human olfactory experience involves active exploration, directed sniffing and nuanced judgements about odour identity, concentrations, and blends, yet to date most compact olfactory displays do not directly support these experiences. We describe the development and validation of a compact, low-cost olfactory display fitted to the hand controller of the HTC Vive Virtual Reality (VR) system that employs stepless valves to enable control of scent magnitude and blending (Fig. 1). Our olfactory display allows for concealed (i.e., unknown to the user) combinations of odours with virtual objects and contexts, making it well suited to applications involving interactions with odorous objects in virtual space for recreational, educational, scientific, or therapeutic functions. Through a user study and gas sensor analysis, we have been able to demonstrate that our device presents clear and consistent scent output, is intuitive from a user perspective, and supports gameplay interactions. We present results from a smell training game in a virtual wine tasting cellar in which the initial task of identifying wine aroma components is followed by evaluating more complex blends, allowing the player to "level up" as they proceed to higher degrees of connoisseurship. Novice users were able to quickly adapt to the display, and we found that the device affords sniffing and other gestures that add verisimilitude to olfactory experience in virtual environments. Test-retest reliability was high when participants performed the task two times with the same odours. In sum, the results suggest our olfactory display may facilitate use in game settings and other olfactory interactions.